A three layer design with mesoporous silica encapsulated by a carbon core and shell for high energy lithium ion battery anodes. Issue 45 (13th October 2015) - Cao, Xi; Chuan, Xiuyun; Massé, Robert C.; Huang, Dubin; Li, Shuang; Cao, Guozhong
Abstract : A novel C/SiO2 composite with a carbon–silica–carbon (C-mcms) three layer structure was synthesized and evaluated as an anode material for high-energy lithium ion batteries. The C-mcms exhibits an excellent capacity of about 1055 mA h g −1 at a current density of 500 mA g −1 after 150 cycles without detectable decay, and high-rate capability. Abstract : A novel C/SiO2 composite with a carbon–silica–carbon (C-mcms) three layer structure was synthesized and evaluated as an anode material for high-energy lithium ion batteries. The C-mcms exhibits an excellent capacity of about 1055 mA h g −1 at a current density of 500 mA g −1 after 150 cycles without detectable decay, and high-rate capability, which is superior to other similar composites without the carbon core or the carbon shell. The results indicate the structural effect on the enhancement of the electrochemical properties: the SiO2 nanoparticles are completely confined between the carbon shell and the carbon core; the two carbon parts work together to keep the structural integrity and to keep the electrode highly conductive and active during cycling, which guarantees high capacity and cycle stability; the interior pores and voids among the SiO2 nanoparticles can provide free space to accommodate the volume change and buffer the volume effect of the electrode during lithiation/delithiation.